2017
DOI: 10.3390/en10040540
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Based Drilling Fluids: A Review

Abstract: Nanomaterials are engineered materials with at least one dimension in the range of 1-100 nm. Nanofluids-nanoscale colloidal suspensions containing various nanomaterials-have distinctive properties and offer unprecedented potential for various sectors such as the energy, cosmetic, aerospace and biomedical industries. Due to their unique physico-chemical properties, nanoparticles are considered as very good candidates for smart drilling fluid formulation, i.e., fluids with tailor-made rheological and filtration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
110
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(120 citation statements)
references
References 66 publications
3
110
0
Order By: Relevance
“…NP concentration of 0.9 wt% shows a significant improvement in the viscosity, hence it has been considered for the cuttings transport investigations. The effective dispersion ability of NPs within the fluid structure could be the responsible for viscosity improvement 46 . Figure 6 depicts fluid viscosity distribution in the model through a cross‐sectional view of the viscosity contour.…”
Section: Resultsmentioning
confidence: 99%
“…NP concentration of 0.9 wt% shows a significant improvement in the viscosity, hence it has been considered for the cuttings transport investigations. The effective dispersion ability of NPs within the fluid structure could be the responsible for viscosity improvement 46 . Figure 6 depicts fluid viscosity distribution in the model through a cross‐sectional view of the viscosity contour.…”
Section: Resultsmentioning
confidence: 99%
“…In the recent past, there have been a number of reports pertaining to the application of nanoparticles for oil and gas industry applications [10][11][12][13][14][15][16]. A typical water based drilling fluid is formulated using a variety of chemicals such as viscosifier, fluid loss control additive, shale stabilizer, lubricant, H 2 S scavenger, oxygen scavenger, biocide, etc.…”
Section: Application Of Nanomaterials In Drilling Fluidsmentioning
confidence: 99%
“…Nowadays, for an intensification of heat transfer within different engineering systmes the nanosized metal or metal oxide particles are used [11][12][13]. Different experimental studies showed that an inclusion of nanoparticles of low concentration can improve the heat transfer performance inside the system [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…12 illustrate the effects of heater location, thermal conductivity ratio, nanoparticles concentration and Rayleigh number on the average Nusselt number, nanoliquid circulation rate and heater average temperature.…”
mentioning
confidence: 99%